Entrepreneurial orientation and performance in Malaysian family firms - Chua, Erica Ning Jia (2019)
Family business is one of the main contributors to the country’s economy. As it has different dynamics compared to nonfamily businesses; a lot of researches have been done on the family business factors such as family succession, corporate governance, family ownership and performance. To strive in the current market, the family firm with all their complexities would need to be more entrepreneurial in their activities to improve their firm performance. This paper intends to investigate the relationship between entrepreneurial orientation (EO) and family firm performance. At the same time, as the situation changes the paper would also look into the moderation effect of the environment and the relationship of entrepreneurial orientation and family firm performance. For the data collection, questionnaires were distributed via mail to the respondents in the country. A total of 350 Malaysian family firms where studied using the PLS-SEM software to analyse the data. The main findings of the research revealed that all the five factors of entrepreneurial orientation which are innovativeness, proactiveness, risk taking, autonomy and competitive aggressiveness have a positive relationship with family firm performance. On the other hand, the only factor that is moderated by environmental dynamism and family firm performance would be proactiveness. The study contributes theoretical, methodological to the family theory as well as managerial implication. The limitations and future suggestions were also included in the research.